Vegetation Dynamics and its Response to Climate Change in the Yellow River Basin, China - Zhan, Cun; Liang, Chuan; Zhao, Lu; Jiang, Shouzheng; Niu, Kaijie; Zhang, Yaling; Cheng, Long (Frontiers in Environmental Science, 2022)
As an important ecological corridor, the Yellow River basin (YRB) is crucial for the eco-environmental security and sustainable socio-economic development of China. Systematic studies on the spatiotemporal evolution of vegetation cover and the response of vegetation dynamics to climate change in the YRB at different timescales are lacking. Utilizing a long-term remotely sensed Normalized Difference Vegetation Index (NDVI) and gridded climate dataset, we examined the spatiotemporal variability of vegetation cover and its response to climate variables in the Yellow River Basin (YRB) at multiple timescales by using the Mann-Kendall test, rescaled range analysis, and partial correlation analysis. Results indicated that the annual NDVI in the YRB decreased spatially from southeast to northwest, and peaked in August with the year. From 1982 to 2015, the YRB experienced greening during the annual, growing season and spring, with statistically significant NDVI increases (p < 0.05) recorded in over 55% of the vegetated areas. NDVI trends should be expected to persist in the future, as evidenced by the Hurst index exceeding 0.5 in over 85% areas of the YRB. Temperature and precipitation determined the spatiotemporal pattern of vegetation cover in the YRB, and vegetation dynamics response to climatic variations varied among seasons and climatic zones. In contrast to other seasons, spring NDVI was significantly correlated with temperature, whereas winter vegetation was more vulnerable to suppression by increased precipitation. Vegetation growth was more susceptible to precipitation than to temperature in the arid and semiarid zones, while temperature dominated vegetation dynamics in the semi-humid zone, and the sunshine duration was essential for vegetation growth in high-altitude regions. The study contributes to a deeper understanding of the interrelationship between vegetation dynamics and climate change in the YRB and provides useful suggestions for the regional ecological conservation in the context of global warming.